J.-M. G. Le Clézio: Ressonâncias surrealistas - Camarani, Ana Luiza Silva [UNESP] (My University, 2010)
Concentrating on three works by Le Clezio - the novel Voyages de l'autre côté (1975), the essay L'Inconnu sur la terre (1978) and the short story Lullaby, this last one included in the short story collection titled Mondo et autres histories (1978) -, this paper aims at focusing on the dialogs these texts establish with the surrealist literature when they make the hidden real emerge and determine an expanded reality.
J.-M. G. Le Clezio: Surrealist resonances
Keywords: French literature; Intertextuality; Narrative; Poetry